Effects of Fe3O4 Nanoparticle Stress on the Growth and Development of Rocket Eruca sativa. (28th April 2019) - Plaksenkova, Ilona; Jermaļonoka, Marija; Bankovska, Linda; Gavarāne, Inese; Gerbreders, Vjačeslavs; Sledevskis, Eriks; Sniķeris, Jānis; Kokina, Inese
Abstract : Plants exposed to stress use the variety of gene regulatory mechanisms to achieve cellular homeostasis, including posttranscriptional regulation of gene expression where microRNAs (miRNAs) play a pivotal role. Since various environmental stress factors such as nanoparticles affect crop productivity and quality, the aim of the present study was to evaluate the genotoxicity level and to estimate miRNA expression level and chlorophyll a level in the magnetite (Fe3 O4 ) nanoparticle-stressed rocket ( Eruca sativa Mill.) seedlings grown in hydroponics. Rocket seedlings were exposed to 1 mg/L, 2 mg/L, and 4 mg/L Fe3 O4 nanoparticles, and after 5 weeks, seed germination rate, root-shoot elongation, genotoxicity, chlorophyll a, and miRNA expression levels were evaluated. The obtained results indicated that 1 mg/L, 2 mg/L, and 4 mg/L concentrations of Fe3 O4 nanoparticles induce low genotoxicity and have a positive effect on the growth and development of rocket seedlings and that nanoparticles may improve the ability of plants to stand against environmental stresses.